Green Fabrication and Characterization of Zinc Oxide Nanoparticles using Eucalyptus Leaves for Removing Acid Black 210 Dye from an Aqueous Medium - Najm, Zahraa A.; Shakorfow, Abdelmalik Milad; Al Mhanna, Najah; Hassan, Ahmed K.; Atiya, Mohammed A. (Al-Khwarizmi Engineering Journal, 2023)
This study uses an environmentally friendly and low-cost synthesis method to manufacture zinc oxide nanoparticles (ZnO NPs) by using zinc sulfate. Eucalyptus leaf extract is an effective chelating and capping agent for synthesizing ZnO NPs. The structure, morphology, thermal behavior, chemical composition, and optical properties of ZnO nanoparticles were studied utilizing FT-IR, FE-SEM, EDAX, AFM, and Zeta potential analysis. The FE-SEM pictures confirmed that the ZnO NPs with a size range of (22-37) nm were crystalline and spherical. Two methods were used to prepare ZnO NPs. The first method involved calcining the resulting ZnO NPs, while the second method did not. The prepared ZnO NPs were used as adsorbents for removing acid black 210 dye (AB210) from simulated wastewater. The removal efficiency using calcinated and uncalcinated ZnO NPs was 57 % and 59 %, respectively.